2020
DOI: 10.3390/ijms21155361
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel High-Resolution Size-Guided Turbidimetry-Enabled Particle Purification Liquid Chromatography (PPLC): Extracellular Vesicles and Membraneless Condensates in Focus

Abstract: Acellular particles (extracellular vesicles and membraneless condensates) have important research, drug discovery, and therapeutic implications. However, their isolation and retrieval have faced enormous challenges, impeding their use. Here, a novel size-guided particle purification liquid chromatography (PPLC) is integrated into a turbidimetry-enabled system for dye-free isolation, online characterization, and retrieval of intact acellular particles from biofluids. The chromatographic separation of particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 88 publications
2
45
0
Order By: Relevance
“…Additional studies with increased sample size are needed to examine the relationship between EV surface charge and microbial products contents in people living with HIV (PLWH). Furthermore, what is warranted is the use of purer EV preparations such as those isolated by particle purification liquid chromatography (PPLC) [96], since the EVs described in this study were isolated using the precipitation method. Other questions that remain unanswered include (i) why the ζ-potential of BEV differ from SEV?…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies with increased sample size are needed to examine the relationship between EV surface charge and microbial products contents in people living with HIV (PLWH). Furthermore, what is warranted is the use of purer EV preparations such as those isolated by particle purification liquid chromatography (PPLC) [96], since the EVs described in this study were isolated using the precipitation method. Other questions that remain unanswered include (i) why the ζ-potential of BEV differ from SEV?…”
Section: Discussionmentioning
confidence: 99%
“…Still, many impurity proteins co-isolated with exosomes during ultracentrifugation were found in the second and third peaks after size-exclusion chromatography [ 62 ]. Thus, gel filtration is an advantageous approach for the additional effective purification of exosomes from impurities, but there is still room for improvement [ 63 ].…”
Section: Methods Of Exosome Isolationmentioning
confidence: 99%
“…The group investigated the effects of HIV-1 infection and illicit drug use on the structure and function of SEVs, and concluded that HIV-SEV, Drug-SEV, and HIV-Drug-SEV may mediate pathological processes by differentially inducing monocytes' actin-cytoskeletal re-organization, adhesion, ECM-modifying metalloprotease secretion, and chemotactic migration toward HIV secretome [108]. Lessons from study [108] led the group to develop a gradient SEC (gSEC) column in which all available Sephadex beads (Table 1) were layered in a 100 x 1 cm column [109]. The gSEC column yielded four distinct peaks, the first two of which correspond to two (large and small) EV populations, the third peak was enriched in membraneless condensates, comprising small RNAs and a unique protein signature, but clearly lacking a membrane whereas the fourth contained small molecules and salts [109].…”
Section: Semenmentioning
confidence: 99%
“…Lessons from study [108] led the group to develop a gradient SEC (gSEC) column in which all available Sephadex beads (Table 1) were layered in a 100 x 1 cm column [109]. The gSEC column yielded four distinct peaks, the first two of which correspond to two (large and small) EV populations, the third peak was enriched in membraneless condensates, comprising small RNAs and a unique protein signature, but clearly lacking a membrane whereas the fourth contained small molecules and salts [109]. Thus far, seminal plasma is one of the highest EV-containing body fluids, with diverse cargos and functions [61,110-113].…”
Section: Semenmentioning
confidence: 99%
See 1 more Smart Citation